Overcoming water scarcity and quality constraints: Integrated Management of Water in River Basins - Svendsen, Mark (International Food Policy Research Institute, 2001)
Until the beginning of the 19th century, human water use was limited. Natural features and forces largely dictated river flow regimes, and natural biota were the primary water users. By the 20th century, a great remaking of river systems occurred as humans manipulated the natural hydrology to meet the domestic supply, sanitation, food, fiber, and industrial needs of growing populations and rising standards of living.